Pembiasaan Shalat Tepat Waktu untuk Mengembangkan Karakter Disiplin Anak - Mauizah Hanifah; Silvi Novtrianti; Zahrah Nabila; Firman Syaputra; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research was motivated by the problem of children's lack of religious ability in time management, especially in terms of not wasting time, making good use of time, and providing an example to their children. The aim of this research is to find out whether forming a disciplined character by praying on time has an effect or not. The research methods used in this article are qualitative and quantitative research methods. In this research, we will use several steps to obtain relevant data. First, determining the research location will be carried out in several schools in representative areas. This location selection aims to obtain diverse data and reflect different conditions. The research concludes that the result of this article is to form a disciplined character in children through the habit of praying on time, which is very effective and efficient. And in fact, when children manage their own time, they show signs of discipline. This is proof that praying on time is related to a person's quality.